Equity and social exchange in dating couples associations with satisfaction, commitment and stability - Sprecher,Susan ([Place of publication not identified] National Council on Family Relations, 2001)
A longitudinal study with romantic couples was conducted to examine the importance of equity relative to other social exchange variables (i.e., rewards, investments, and alternatives) in predicting relationship satisfaction, commitment, and stability. Under benefiting inequity (but not over benefiting inequity) was associated with a lower level of satisfaction and commitment and a greater likelihood of breakup. However, little evidence was found that equity at one time predicted change in satisfaction and commitment. Slightly more evidence was found for a reverse causal direction: Satisfaction and commitment contributed to a decrease in under benefiting inequity, although these results were not consistent across time. Women's commitment was the strongest predictor of relationship stability. In addition, women's under benefiting inequity and alternatives and men's alternatives were associated with breakups in some of the analyses, and women's rewards and satisfaction and men's satisfaction were associated with relationship stability in some of the analyses. Because of the multiple waves and the extended length of the longitudinal study, the findings make a unique contribution to the literature on equity and exchange.
Includes bibliographical references.
Keywords: Dating (Social customs).